EFFECTIVENESS OF COMMUNITY-BASED PSYCHOSOCIAL SUPPORT FOR CHILD DISASTER VICTIMS IN PIDIE JAYA IN 2026 - Sri Wahyuni; Aris Winandar (MEDALION Journal: Medical Research, Nursing, Health and Midwife Participation, 2026)
Disaster flood flash floods that hit Pidie Jaya Regency at the end of November 2025 resulted in thousands family evacuate and cause impact serious psychological problems , especially in children . Research This aim For analyze effectiveness of support programs psychosocial based community for children victims of the disaster in Pidie Jaya in 2026. Research design using quasi-experimental pre- post test with control group with involving 100 children 6–15 year olds who were flood victims Bandang . Intervention support psychosocial based community implemented during eight Sunday includes Psychological First Aid (PFA), therapy play , art therapy, group peers , and education caregivers . Children's mental health measured using the Strengths and Difficulties Questionnaire (SDQ). Results showed a significant decrease in the total difficulty score from 24.5±4.1 to 15.0±3.2 (p=0.000). Play therapy showed the highest percentage of improvement (82.1%), followed by art therapy (79.6%) and PFA (78.4%). The involvement of community leaders and caregivers strengthened the sustainability of the intervention. Community-based psychosocial support has been proven effective in restoring the mental health of disaster-affected children in Pidie Jaya.